The Paradoxes of Transparency: Science and the Ecosystem Approach to Fisheries Management in Europe - Douglas Clyde Wilson (Amsterdam University Press, 2010)
The International Council for the Exploration of the Sea (ICES) is the central scientific network within the massive set of bureaucracies that is responsible for Europe's Common Fisheries Policy (CFP). While spending the past 25 years failing to sustain Europe's fish stocks, this management system also became adept at making the lives of its scientists miserable. Now it is being confronted by the complex challenge of an ecosystem-based approach to fisheries management. If this combination of a multi-national bureaucracy, hard politics, and scientific uncertainty has made it impossible to maintain many individual fish stocks, how are decisions going to be made that consider everything from sea birds to climate change? The old political saw that "if you can't solve a problem, make it bigger" has never been put to a test like this! Yet ICES has begun to rise in an impressive way to the scientific challenge of providing advice for an ecosystem approach within the world's most cumbersome fisheries management system. This book lays out the results of extensive sociological research on ICES and the decision making systems into which it feeds. ICES is finding ways to provide effective advice in the many situations where scientific advice is needed but a clear, simple answer is out of reach. In spite of the difficulties, scientists are beginning to help the various parties concerned with management to deal with facts about nature in ways that are more useful and transparent.
Keywords: 330; Public administration; Fischerei; Management; EU-Fischereipolitik; Operations Research; Wissenschaft; Internationale Organisation